Current practices and institutional arrangements in breeding by CGIAR – NARS - Nchanji, Eileen Bogweh; Teeken, Bela; Webber, Hope; Pede, Valerien; Teeken, Béla (Bioversity International and the International Center for Tropical Agriculture, 2023)
The Consultative Group on International Agricultural Research (CGIAR) market intelligence initiative aims to bring together inclusive and strategic information on future crops’, market segments, and trait priorities that sharpen crop breeding investments aligned to the needs and preferences of farmers, agri-business and consumers by engaging public and private sector partners toward stronger crop breeding partnerships to benefit farmers across the globe. "The results presented here are from seven key informant interviews with NARS and CGIAR breeders and crop leads from Sub-Saharan Africa"